Holy Conversation : Spirituality for Worship - Linman, Jonathan, 1961- (Book collections on Project MUSE., 2010)
Linking the themes of spirituality and worship and giving each needed focus in ways that are biblically and theologically rich and consistent with ecumenical traditions, this book specifically explores the relationship of sacred reading (lectio divina) to worship. Linman sees this practice as one element in the larger liturgical action of Gathering, Word, Meal, and Sending. Our "spiritual worship" (cf. Rom 12:1), he argues, is the holy conversation between worshipers and the triune God who leads us to greater participation in Christ and to transformation through Christ's presence.